PERAN ULAMA SEBAGAI OPINION LEADER DI PEDESAAN DALAM MENGHADAPI INFORMASI HOAKS - Dadang Sugiana; Ira Mirawati; Putri Trulline (Avant Garde, 2019)
Ulama is one of the opinion leaders in rural areas. Based on Two Step Flow Communication theory, they should be the information disseminator and legitimator for the community. However, is they still conduct that role in this digital era? Can Ulamas provide true information and play a role in counteracting hoaxes circulating through digital media? This study used descriptive methods with interviews as a data collection tool. The research informants were 17 Ulamas, 30-78 years old in Kecamatan Parigi, Kabupaten Pangandaran. The results shows that the majority of Ulamas over 50 years old do not have a smartphone, only a few of them have smartphones and have WhatsApp features as well as Facebook. They are not active in using it and are not at the forefront of knowing the latest issues circulating on social media. Communities in rural areas still make Ulamas as opinion leaders but not on news that develops on social media. Therefore, Ulama still have an important role in confirming hoax circulating on social media but their source of knowledge is not the internet but still guided by the Qur'an and printed holy books. These Ulamas argue that if the truth and benefits are unclear, they may not disseminate a message obtained from the internet. Ulama realize that information technology has developed greatly, but they argue that they do not need to preach about it. The problem of the community around them is the real problem that the solution is also through real discussion and communication.